Evaluation of the effect of organic soil amendments and irrigation regimes on the quantitative aspects of fatty acids in camelina seeds - Mohsenpour, Abbas; Janmohammadi, Mohsen; Shekari, Fariborz; Sabaghnia, Naser (Acta Biologica Szegediensis, 2025)
This study aimed to assess the impact of soil moisture regimes (FI: full irrigation throughout the growing season, DI: deficit irrigation at 60% of field capacity during vegetative growth) and farmyard manure (FYM) levels (F0: 0, F10: 10, and F20: 20 t ha-¹) on the fatty acid profile of oil extracted from camelina seeds in the Razan region, western Iran. The highest linolenic acid content was recorded under FI+F10 and DI+F10 conditions. The application of F10 under FI and DI increased linoleic acid content by 2% and 1.4%, respectively. Water deficit stress significantly reduced eicosadienoic acid content (by 0.95%). The highest eicosadienoic acid content was observed under FI+F20 conditions (14.53%). Soil amendments and irrigation improved oleic acid content by approximately 3%. The highest palmitic acid content (5.20%) was obtained with F10 and F20 under FI conditions. Erucic acid content decreased under both soil moisture regimes as FYM application increased. The highest saturated fatty acid content was recorded under FI+F20. Plants grown with F20 had the highest polyunsaturated fatty acid content (69%).